Systematic literature review to inform the Portuguese recommendations for the management of Raynaud's phenomenon and digital ulcers in systemic sclerosis and other connective tissue diseases - Costa, Emanuel (2024)
OBJECTIVE: To perform a systematic literature review (SLR) aimed at evaluating the efficacy and safety of pharmacological and non-pharmacological treatments for Raynaud's phenomenon (RP) and digital ulcers (DU) in patients with systemic sclerosis (SSc) and other connective tissue diseases (CTD), in order to inform the Portuguese recommendations for managing RP and DU in these patients. METHODS: A SLR was conducted until May 2022 to identify studies assessing the efficacy and safety of pharmacological and non-pharmacological interventions for RP and DU in SSc and other CTD. Eligible study designs included randomized controlled trials (RCTs), controlled clinical trials, and their extensions for assessing efficacy and safety of interventions. Observational studies with a comparator were included for evaluating the efficacy and safety of non-pharmacological interventions and safety of pharmacological interventions. The risk of bias of each study was assessed using standard tools. RESULTS: Out of 71 publications meeting the inclusion criteria, 59 evaluated pharmacological and 12 non-pharmacological interventions. We found moderate quality evidence supporting the efficacy of calcium channel blockers, phosphodiesterase-5 inhibitors, and intravenous prostacyclin analogues in reducing RP frequency, severity, and duration. Intravenous iloprost had a small to moderate effect size in improving DU healing. Phosphodiesterase-5 inhibitors were effective in reducing total DU count, new DU occurrence, and enhancing DU healing. Bosentan effectively prevented new DU in SSc patients. No new safety concerns were associated with these treatments. The studies on non-pharmacological interventions were, in general, of low quality, and had a small sample size. Warming measures decreased frequency and duration of RP attacks; laser therapy improved RP-related outcomes; local oxygen-ozone therapy improved RP outcomes as an add-on therapy; bone marrow mononuclear cell implantation improved DU-associated pain; periarterial sympathectomy and vascular bypass reduced DU number and finger amputation risk. CONCLUSION: The available evidence supports the efficacy and safety of pharmacological interventions, namely nifedipine, sildenafil, iloprost, and bosentan in treating RP and DU in patients with SSc and other CTD. Scarce and low-quality evidence does support the use of some non-pharmacological interventions but with only a modest effect size. This SLR underscores the limited availability of high-quality evidence for determining the optimal treatment.